Diurnal and stress‐induced intra‐hippocampal corticosterone rise attenuated in 11β‐HSD1‐deficient mice: a microdialysis study in young and aged mice. (23rd January 2015) - Yau, Joyce L. W.; Noble, June; Kenyon, Christopher J.; Ludwig, Mike; Seckl, Jonathan R.
Abstract: 11β‐Hydroxysteroid dehydrogenase type 1 (11β‐HSD1) locally regenerates active glucocorticoids from their inert forms thereby amplifying intracellular levels within target tissues including the brain. We previously showed greater increases in intra‐hippocampal corticosterone (CORT) levels upon Y‐maze testing in aged wild‐type than in 11β‐HSD1 −/− mice coinciding with impaired and intact spatial memory, respectively. Here we examined whether ageing influences 11β‐HSD1 regulation of CORT in the dorsal hippocampus under basal conditions during the diurnal cycle and following stress. Intra‐hippocampal CORT levels measured by in vivo microdialysis in freely behaving wild‐type mice displayed a diurnal variation with peak levels in the evening that were significantly elevated with ageing. In contrast, the diurnal rise in intra‐hippocampal CORT levels was greatly diminished in 11β‐HSD1 −/− mice and there was no rise with ageing; basal intra‐hippocampal CORT levels were similar to wild‐type controls. Furthermore, a short (3 min) swim stress induced a longer lasting increase in intra‐hippocampal CORT levels in wild‐type mice than in 11β‐HSD1 −/− mice despite no genotypic differences in elevation of plasma CORT. These data indicate that 11β‐HSD1 activity contributes substantially to diurnal and stress‐induced increases in hippocampal CORT levels. This contribution is even greater with ageing. Thus, 11β‐HSD1 inhibition may be an attractive target for treating cognitive impairments associated with stress or ageing. Abstract : The diurnal rise in intra‐hippocampal corticosterone (CORT) levels in wildtype mice increased with ageing but was greatly diminished in 11β‐HSD1 −/− mice. A short swim stress induced a greater rise in intra‐hippocampal CORT levels in wildtype than 11β‐HSD1 −/− mice; effects were more pronounced with ageing. These data indicate that 11β‐HSD1 activity contributes substantially to diurnal and stress‐induced increases in hippocampal CORT levels.